Optimizing biological treatment of petroleum industry wastewater in a facultative stabilization pond for simultaneous removal of carbon and phenol. (3rd April 2021) - Almasi, Ali; Mahmoudi, Mojtaba; Mohammadi, Mitra; Dargahi, Abdollah; Biglari, Hamed
Abstract: Oil wastewater industries create big problems for receiving sources due to the presence of a variety of compounds including linear and cyclic hydrocarbons, recalcitrant materials and toxic compounds, if they are discharged into the environment without proper treatment. In this study, Simultaneous removal of carbon and phenol from oil refinery wastewater was studied in a facultative stabilization pond facultative as a natural and economic system. Experiments were designed and analyzed based on response surface method and the central composition of the organization. Hydraulic retention time (4–10 days) and phenol concentration (100–300 mg/L) were selected for analysis, optimization and modeling of the process and 5 parameters related to removal of TCOD, SCOD, TBOD5, SBOD5, and phenol were measured as process responses. According to results, reaction time was shown to be the most important variable showing incremental effect on the pond in a way that the maximum removal efficiency of carbon and phenol was achieved in retention time of 10 days. Phenol concentration showed inverse and negative relationship with the efficiency of the system in such a way that the minimum removal efficiency was obtained at a concentration of 300 mg/L. Linear and quadratic models indicated the system behavior. According to these results, facultative stabilization pond has a considerable capability in removing phenol from the wastewater of oil industry if it is operated properly and desirably. Thus, It could be considered as an efficient and economical choice, in particular, in developing countries.